UIN Makassar Curriculum Reform: Encouraging Graduates' Technical Competencies in Line with Job Market Demands - Fatimah Abd Rahman (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2026)
This policy paper examines the crucial issue of the inability of the curriculum and learning process at UIN Alauddin Makassar to produce graduates with relevant and ready-to-use technical competencies according to the demands of the job market. The root causes of the policy problems identified include: (1) Curriculum gaps due to the dominance of theoretical content, (2) Lack of active involvement of the industrial world in curriculum formulation, and (3) Cultural differences and priorities between academics and practitioners. This condition creates negative externalities in the form of a high skills gap and low employability of graduates, which are not in line with the mandate of the KKNI and the principles of Educational Accountability. The methodology used is a qualitative-normative policy analysis with three main stages: (1) Problem Identification through the synthesis of literature and empirical issues; (2) Critical Analysis, which includes the use of theoretical frameworks such as Human Capital Theory, Triple Helix Model, and T-Shaped Professionals Concept, as well as a review of supporting laws and regulations (Law No. 12/2012, Permendikbudristek No. 53/2023, and UINAM Rector's Decree regarding the curriculum); and (3) Formulation of Alternatives and Recommendations, which involves evaluation using William N. Dunn's Scoring Theory to determine the feasibility of the policy.